2017
DOI: 10.1007/s10792-017-0668-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glycosylated hemoglobin on the choroidal thickness

Abstract: Serum HbA1c levels were not correlated with foveal choroidal thickness. Choroidal thickness is effected by several factors as axial length, age and systemic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…In agreement with other studies, DM duration had no significant correlations with CT(s) and CV(s) in our series [ 15 , 22 , 32 ]. According to our findings, FBS had no association with CT or CV.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with other studies, DM duration had no significant correlations with CT(s) and CV(s) in our series [ 15 , 22 , 32 ]. According to our findings, FBS had no association with CT or CV.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, we found that there was no significant correlation between the duration of diabetes and choroidal thickness. This is compatible with the studies of Sahinoghlu-Keskek et al and Shen et al [23,26]…”
Section: Discussionsupporting
confidence: 93%
“…Sahinoglu-Keskek et al classified 122 eyes of 122 diabetic patients into three study groups including diabetic patients without DR, diabetic patients with DR and no macular edema, and diabetic patients with DR and macular edema. [23] They reported that the sub-foveal choroid in patients with no DR was significantly thicker than that in patients with DR and without macular edema. Moreover, they reported that no significant differences in HbA1c levels were detected among the three study groups and concluded that there was no correlation between sub-foveal choroidal thickness and HbA1c values.…”
Section: Discussionmentioning
confidence: 99%
“…The Beijing Eye Study reported that the glucose level did not affect subfoveal CT, but HbA1c was not determined in that study. Sahinoglu-Keskek et al 31 found no correlation between HbA1c and subfoveal CT. Our study confirmed that macular CT was not independently associated with HbA1c. Jonas et al 32 reported that subfoveal CT was significantly associated with BCVA after adjusting for age, sex, AL, and corneal curvature in the normal population.…”
Section: Discussionmentioning
confidence: 95%